2021
DOI: 10.1016/j.breast.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of the 21-gene assay in predicting response to neoadjuvant endocrine therapy in breast cancer: A systematic review and meta-analysis

Abstract: Introduction: OncotypeDX© Recurrence Score (RS) is a multigene panel used to aid therapeutic decision making in early-stage, estrogen receptor positive (ERþ)/human epidermal growth factor receptor-2 negative (HER2-) breast cancer. Aim: To compare responses to neoadjuvant endocrine therapy (NET) in patients with ERþ/HER2-breast cancer following substratification by RS testing. Methods: This systematic review was performed in accordance to the PRISMA guidelines. Studies evaluating pathological complete response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
(76 reference statements)
0
27
0
Order By: Relevance
“…The solution for the ILC cohort, which have a strong tendency towards hormone positivity, may be a more widespread use of Neoadjuvant Endocrine Therapy (NET); in their review, Sella et al. reported that NET prescription is underutilised despite its capabilities of achieving tumour downstaging in select cases, indicating that NET may have a more conventional use in prospective HR + breast cancer management [ 83 , 84 ]. Similarly, Davey et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution for the ILC cohort, which have a strong tendency towards hormone positivity, may be a more widespread use of Neoadjuvant Endocrine Therapy (NET); in their review, Sella et al. reported that NET prescription is underutilised despite its capabilities of achieving tumour downstaging in select cases, indicating that NET may have a more conventional use in prospective HR + breast cancer management [ 83 , 84 ]. Similarly, Davey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Davey et al. illustrated the efficacy of NET following low-risk substratification using the 21-gene recurrence score expression assay in the setting of locally advanced estrogen receptor positive breast cancers in their recent meta-analysis [ 84 ]. Similar to the results of the current study, these previous authors highlight the value of NET as a modern management strategy of HR + breast cancers, particularly in the setting of double hormone positive (ER+/PR+) lobular disease as has been previously outlined in cases of low-risk disease [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable funding, investment and resource distribution into the investigation of miRNA as reliable and reproducible clinical biomarkers in breast cancer research and treatment, we are yet to undercover novel biomarkers which can rival the principal ER, PgR, and HER2 receptors to inform breast cancer diagnosis, prognosis and therapeutic strategies. Since the emergence of the molecular era, genomic signatures such as the 21-gene assay and the Mammaprint© 70-gene assay (Agendia, Amsterdam, The Netherlands) has reliably and reproducibly informed prognoses, refined therapeutic systematic chemotherapy prescription and facilitated personalised cancer treatment in early-stage luminal diseases [ 84 , 85 , 86 , 87 , 88 ]. The identification and characterisation of miRNA expression which are as reliable and reproducible as these genomic panels limit current hypotheses, suggesting miRNAs may be impactful biomarkers in malignancy [ 89 ].…”
Section: Limitations and Challenges Of Mirnas As Biomarkersmentioning
confidence: 99%
“…The subsequent results of the TAILORx trial illustrated no survival advantage for post-menopausal patients, with RS < 25, implicating indication for endocrine therapy alone for these patients [ 28 ]. In more recent times, the expansion of indications into the locally advanced and neoadjuvant settings is likely based on preliminary data from the RxPONDER trial (recruiting patients with 1–3 positive nodes) and several meta-analyses [ 29 , 30 , 31 , 32 ]. The landmark clinical studies assessing the role of multigene expression assays for guiding adjuvant chemotherapy prescription in ER+ breast cancer are outlined in Supplementary Table S1 .…”
Section: Breast Cancer Chemotherapymentioning
confidence: 99%
“…However, the paradigm has evolved such that intrinsic tumour biology informs response rates to neoadjuvant therapies and predicts those likely to achieve pCR [ 62 ]. While molecular subtyping from diagnostic core biopsy remains critical in contemporary breast cancer management in relation to the indication for NAC, multigene expression assays (such as the 21-gene expression signature) are likely to indicate response to neoadjuvant therapies in early stage ER+ disease [ 29 , 30 ] ( Supplementary Figure S1 ). With respect to HER2+ and TNBC, the clinical utility of NAC has become embedded into best-practice guidelines: A recent update from ASCO recommends the use of NAC and trastuzumab for HER2+ cancers (with the exception of T1a-T1b N0 disease), with anthracycline and taxane-based chemotherapy and trastuzumab to be utilised in high-risk LN- cases and those with LN positivity [ 63 ].…”
Section: Breast Cancer Chemotherapymentioning
confidence: 99%